Association between Insulin Resistance and Hyperandrogenism among Women with PCOS in Pakistan - Muhammad Faheem, Muaaz Bin Saif, Labiqa Afzaal, Maira Iqbal, Aleena Nazar, Afeefa Shaheera Iqbal, Hira Zaheer Chughtai, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder in women of reproductive age and is frequently associated with insulin resistance and hyperandrogenism. Insulin resistance plays a pivotal role in aggravating androgen excess and contributes to both reproductive and metabolic complications. Evidence from Pakistani populations regarding this relationship remains limited. Objective: To assess the association between insulin resistance and hyperandrogenism among women diagnosed with PCOS in Pakistan. Methods: This cross-sectional analytical study was conducted at Sheikh Zayed Hospital, Lahore, and Arif Memorial Teaching Hospital, Pakistan, from January 2023 to May 2024. A total of 90 women aged 18–40 years diagnosed with PCOS according to the Rotterdam criteria were included. Clinical hyperandrogenism was assessed using the modified Ferriman–Gallwey score, while biochemical evaluation included fasting glucose, insulin, total testosterone, and sex hormone-binding globulin levels. Insulin resistance was determined using the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Statistical analysis was performed to evaluate correlations between insulin resistance and hyperandrogenic parameters. Results: Insulin resistance was observed in 64.4% of participants. Significant positive correlations were found between HOMA-IR and total testosterone, free androgen index, and modified Ferriman–Gallwey score, while a significant inverse correlation was observed with sex hormone-binding globulin levels (p < 0.001). These associations remained significant after adjustment for body mass index. Conclusion: Insulin resistance is highly prevalent among Pakistani women with PCOS and shows a strong independent association with hyperandrogenism. Early metabolic screening and targeted interventions may help reduce disease severity and long-term metabolic complications. Keywords: Polycystic, Insulin, Hyperandrogenism, Resistance, Metabolism